What makes a good political leader?:Young people’s perceptions from the Republic of Sakha (Yakutia) - Ivanova, Aytalina; Okorokova, Matrena; Stammler, Florian; Wilson, Emma (Routledge, 2020)
This chapter analyses data from research carried out among young Indigenous people in the Republic of Sakha (Yakutia) to elicit what they perceive to be qualities of a good political leader. We investigate theoretical aspects of the formation of political youth culture and factors influencing the representation of political leadership. Empirical research results from two surveys, supported by qualitative fieldwork, in an urban and a rural setting, reveal young people’s perceptions of what makes an ideal leader. We analyse similarities between urban and rural youth in their ideas about political leadership. Urban students emphasised the importance of the personal qualities of a good political leader, while rural Indigenous youth found professional qualities important. Using categories of political leadership identified by Hermann, we found that the preferred political leader for students studying in the regional capital fits the leadership type of ‘leader-servant’, whereas the rural young people prioritised what is called a ‘leader-fireman’. All together, we find that ideas of political leadership among Indigenous youth follow the Russian mainstream political culture. We argue that this is because politics in the RSY is made within the Russian political system (albeit by local Indigenous politicians) and not by Indigenous politicians according to Indigenous traditional institutions of leadership.